Possibilities of Logistics Policy Improvement - Průša, Petr; Tilkeridis, David (Promet - Traffic&Transportation, 2012)
The paper presents the strategic logistics management with emphasis on clear, accurate and effective material flow from the suppliers and internally, as well as an outline of the logistics policy for continuous improvement. The implementation of a complete Supplier Logistics Performance System is essential to support internal processes efficiency and establish a continuous improvement system according to the main logistics policy. Every company should consider such a system in order to win in the challenging field of current industry.KEY WORDS: logistics policy, logistics continuous improvement system, Electronic Data Interchange (EDI), Logistics Key Performance Indicators (LKPI)